Genesis of the Heiyanshan Tungsten Skarn Deposit in the East Tianshan, NW China: Insights From Geology, Fluid Inclusion, Isotopic Geochemistry and Geochronology - Xue, Dong; Deng, Xiao-Hua; Bagas, Leon; Chen, Xu-An; Wu, Yan-Shuang; Jiang, Xiao (Frontiers in Earth Science, 2021)
The eastern Tianshan Terrane is a highly prospective zone that contains several porphyry Cu–Mo, VMS Cu–Zn, magmatic Cu–Ni, epithermal and orogenic Au deposits. However, the source and evolution of the mineralising fluids related to the skarn W deposits are poorly understood. The Heiyanshan W deposit is hosted by metamorphosed clastic and carbonate beds in the Mesoproterozoic Jianshanzi Formation deposited on a continental margin tectonic setting. The Jianshanzi Formation is intruded by biotite monzogranite that yield weighted 206Pb/238U age of 326.9 ± 1.6 Ma, which suggest that the Heiyanshan W deposit was formed in the Carboniferous. The mineralisation is hosted by a prograde hydrothermal altered zone represented by a garnet (–pyroxene) skarn, and retrograde skarn characterised by fine-grained scheelite. The paragenesis of the Heiyanshan mineralisation can be subdivided into prograde skarn stage, retrograde skarn stage, quartz-sulphide stage and quartz-calcite vein stage. The types of fluid inclusions recognised in the various minerals in the deposits are liquid-rich aqueous, vapour-rich aqueous, and daughter mineral-bearing. The homogenisation temperatures of fluid inclusions from the Heiyanshan deposit decrease from 290 ± 28 °C in garnet, through 232 ± 31 °C in scheelite, to 232 ± 36 °C in quartz and 158 ± 15 °C in non-mineralised calcite, which is typical of W-bearing skarn deposits worldwide. The δ18Owater values from the Heiyanshan deposit range from +4.7 to +6.6‰ in garnet, +1.3 to +1.9‰ in quartz and −6.1 to −4.4‰ in calcite. We have measured δD in fluid inclusions from different minerals, although these bulk analyses are just a mixture of the different FIA’s present in the sample. The δD values of fluid inclusions in garnet, quartz, and calcite are from −121 to −71‰ , −84 to −75‰ and −101 to −82‰, respectively, also indicative of deep-sourced magmatic fluids mixed with meteoric water. The decrease in the homogenisation temperatures for the fluid inclusions at the Heiyanshan deposit is accompanied by a drop in salinity indicating that tungsten-bearing minerals precipitated during fluid mixing between magmatic fluids and meteoric water. We conclude that eastern Tianshan Terrane contains two pulse of tungsten metallogenic events of Late Carboniferous and Early Triassic.